Problems of translating and adapting existing idioms in English and Uzbek - Geldiyeva Khursandoy (Peerian Journals Publishing, 2022)
In addition to simple words in all languages, we use idioms, proverbs, metaphors, and other similar words to make our words colorful and meaningful. Such words are available in all languages. We almost always use such words in our speech, and when we speak or write a message or text, we use these words to make our speech or text effective and beautiful. This article discusses idioms, how to explain Uzbek idioms in English, or how to translate English idioms into Uzbek and how to do it. Questions such as whether the idioms are translated directly or selected according to their meaning are answered. The evidence is also given with a few examples.
Keywords: idiom; meaning; conformity; irony